UTILIZING GOOGLE EARTH ENGINE FOR FLOOD-PRONE AREAS USING THE THRESHOLD METHOD IN PASAMAN REGENCY, WEST SUMATRA PROVINCE: English - Ananda Q-to Paguno; Dian Adhetya Arif; Helfia Edial; Eva Purnamasari (Remote Sensing Technology Study Program, 2025)
This study aims to utilize Google Earth Engine and Sentinel-1 image data to map flood areas using the Threshold method, which is expected to provide accurate information to support flood mitigation and management in the Pasaman region. This study also aims to determine the results of the area affected by disaster-prone areas. Based on the results of the study, researchers have obtained a flood hazard map in 2024 in Pasaman Regency by processing Sentinel-1 image data using the Threshold algorithm which has produced an area in the Vulnerable classification with an area of ​​4,225 Ha, a Moderately Vulnerable classification with an area of ​​9,102 Ha and a Safe classification of 3,818 Ha for Pasaman Regency. From the results of data processing for the flood hazard map in Pasaman Regency, it can be concluded that in 2024 Pasaman Regency experienced quite vulnerable floods.